Hubungan Pengetahuan, Budaya, Lingkungan Tempat Tinggal dan Sosial Ekonomi dengan Pernikahan Dini pada Wanita - Mawarni, Atik; Nurnahariah, Nurnahariah; Nugroho, Djoko; Solekhah, Solekhah (Universitas Ahmad Dahlan, 2019)
Background: Cases of early marriage in Semarang Regency still occurred. The region with the highest number of early marriages in Semarang Regency is Bandungan District with a percentage of women as much as 23.75% and men as much as 46%. This study aims to analyze the relationship of knowledge, culture, environment and socio-economic with early marriage. Method: This research was an explanatory research with a cross-sectional design. The population was all married women recorded at religion affair office in Bandungan Subdistrict from January to December 2017 as many as 259 people. A sample of 74 people was selected by means of proportional random sampling. Data were analyzed with percentage values, Chi-square test and logistic regression. Results: There was a correlation between knowledge (p-value=0.001; Exp (B)=11.141), culture (p-value=0.026; Exp (B)=5.206) and parent income (p-value=0.003; Exp (B)=7.509), with early marriage. Conclusion: There was a correlation between knowledge, culture and income of parents with early marriage. The biggest influence was knowledge, followed by parental income and culture. To reduce early marriage, it is necessary to improve knowledge, income of parents and culture. Knowledge improvement is a priority, it can be done through the Youth Reproductive Health program at junior and senior high school.